Manajemen Keuangan Di Mi Muhammadiyah Tlogorandu Juwiring Klaten - Alviyani, Alviyani, Dr. Mohamad Ali, S.Ag, M.Pd (2016)
Finance is an important issue, especially in schools / madrasah, and financial problems will directly influence the quality of educator. Activities at the school / madrasah can be less than optimal because of financial problems either to hire teachers nor procurement for learning in schools. This study is based on the problem: (a) How is the financial planning process in Tlogorandu Juwiring MI Muhammadiyah of District Klaten Year 2015/2016? (b) How the financial implementation of Tlogorandu Juwiring MI Muhammadiyah of Klaten district Year 2015/2016? (C) How the financial evaluation Tlogorandu Juwiring MI Muhammadiyah districts of Klaten Year 2015/2016? The purpose of this study are (1) Describing the process of financial planning in Tlogorandu Juwiring MI MUhammadiyah of Klaten district in the academic year 2015/2016. (2) To identify and describe the financial performance in Tlogorandu Juwiring MI Muhammadiyah of Klaten district year 2015/2016. (3) To identify and describe the financial evaluation in the academic Tlogorandu MI Muhammadiyah of Klaten district in the academic year 2015/2016. This type of research is a kind of field research, where the data was obtained directly from the field. Methods of data collection are interviews, observation, and document. Meanwhile, to analyze the results of this research using descriptive analysis, which is defined as the troubleshooting procedure with a portrait of an abject/subject based on the facts. The results of this research are: first, the financial management plan in Tlogorandu Juwiring MI Muhammadiyah of Klaten district, starting with the preparation of the meeting RKAM together at the beginning of the school year. Financial planning involves principal, school treasurers and pther educational staffs to prepare ehat activities will be done so that it will be seen how the amaunt of funds that will be needed. Second, implementation of financial management in Tlogorandu Juwiring MI Muhammadiyah of Klaten district, within one year of getting the BOS funds of Rp. 84,000,000, - (Eighty four million rupiah) used to pay for te teachers' salaries, facilities and other infractutures other. Thirdly, evaluation of external management which is done by the Ministry of Religious of Klaten district, while the internal evaluation is done after reporting the current BOS in small meeting every three months.